Physiological causes of transplantation shock on rice growth inhibition and delayed heading - HyeonSeok Lee (Nature Portfolio, 2021)
Abstract Transplanting is an important rice cultivation method; however, transplanting shock commonly affects grain yield, and the mechanisms underlying the inhibition of growth, development, and delayed heading caused by transplanting shock have not yet been clearly elucidated. Here, we investigated the effects of seedling age, temperature, and root damage during transplanting on growth, development, and time to heading, both under artificially controlled and natural day length. Additionally, we investigated the impact of seedling root growth space and the potential mitigating effects of residual seed nutrients on young transplanted seedlings. The delay in heading in transplanted versus directly seeded plants was affected more by growth inhibition during the seedling period than by root damage during transplanting. However, root damage had an effect on the inhibition of leaf and tiller development, and the ratio of leaves to tillers increased because tiller development was inhibited more by transplanting shock compared with leaf development. Based on these findings, we propose factors reflecting the delay in growth due to transplanting shock that should be included for more accurate rice phenology modeling and suggest advantageous seeding conditions and transplanting methods for improved rice cultivation and yield in response to climate change.